DEVELOPMENT OF CLASSPOINT-BASED INTERACTIVE LEARNING MEDIA IN SCIENCE SUBJECTS FOR PRIMARY SCHOOL STUDENTS - Anam, Syaiful; Fatirul, Achmad Noor; Fiantika, Feny Rita (UNDIKMA, 2025)
This research aims to develop ClassPoint-based interactive learning media in science subjects, especially Solar System material in elementary schools. Media development is carried out using the ASSURE model, which includes analysis, design, development, implementation and evaluation stages. The products that have been developed are then validated by experts in the fields of design, materials and media. Next, trials were carried out in stages through small groups, medium groups and large groups to determine the feasibility and effectiveness of the media. The research results show that the use of ClassPoint-based media has a significant positive impact on learning effectiveness. This media is able to increase students' active participation in the learning process through interactive features such as polls, quizzes and direct assessments, which support the creation of two-way interactions between teachers and students. Apart from increasing learning motivation, this media also strengthens students' conceptual understanding of the material being studied. Thus, ClassPoint can be an innovative solution for creating more interesting, interactive and meaningful learning at the basic education level.